Quality of service – expectations and reality - Rytel, Olga (Management and Administration Journal, 2023)
This paper describes a customer’s evaluation of the quality of service. It concerns criteria of evaluation and model of gaps’ quality. It includes an example, which describes an imaginary furniture company.